1992
DOI: 10.1021/ja00034a041
|View full text |Cite
|
Sign up to set email alerts
|

Clathrate formation and molecular recognition by novel chalcogen-cyano interactions in tetracyanoquinodimethanes fused with thiadiazole and selenadiazole rings

Abstract: The intermolecular contacts between chalcogen atoms and cyano lone pairs were found to stabilize the crystalline state by electrostatic interaction. This interaction is one of the sources of the directionality in crystal packing of organic molecules and causes the formation of various types of inclusion lattices in the charge-transfer (CT) crystals of 1-3. By using highly selective formation of CT crystals with substituted aromatic hydrocarbons, particular isomers such as p-xylene or 2,6-dimethylnaphthalene (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
80
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(84 citation statements)
references
References 1 publication
(2 reference statements)
4
80
0
Order By: Relevance
“…19-21 All three benzo-2,1,3-chalcogenadiazoles have been investigated as building blocks in supramolecular design because of their propensity to associate through secondary bonding interactions. 22 This has motivated multiple investigations of the electronic structures of such heterocycles, intended to better understand and improve the properties of the compounds. The accuracy of quantum mechanical calculations for these systems, especially for the derivatives of selenium and tellurium, has been limited by the size of the available basis sets, the inclusion of electron correlation (HF), the choice of exchangecorrelation functional (DFT) and the inclusion of relativistic effects.…”
Section: Introductionmentioning
confidence: 99%
“…19-21 All three benzo-2,1,3-chalcogenadiazoles have been investigated as building blocks in supramolecular design because of their propensity to associate through secondary bonding interactions. 22 This has motivated multiple investigations of the electronic structures of such heterocycles, intended to better understand and improve the properties of the compounds. The accuracy of quantum mechanical calculations for these systems, especially for the derivatives of selenium and tellurium, has been limited by the size of the available basis sets, the inclusion of electron correlation (HF), the choice of exchangecorrelation functional (DFT) and the inclusion of relativistic effects.…”
Section: Introductionmentioning
confidence: 99%
“…23 We have studied electrochemical properties of the dinitrile 2, (SN2)Pyz(CN)2, and found that in MeCN two reversible reduction processes are observed at -0.01 and -1.02 V vs Ag/AgCl (see Figure 3) and in DMSO as an electron-donor solvent the first reduction is shifted to the positive region to +0.08 V vs Ag/AgCl, and in the negative region two overlapping reduction processes can be seen at -0.52 and -0.72 V vs Ag/AgCl. The obtained value of the 1 st reduction potential for (SN2)Pyz(CN)2 (2) is comparable with such strong -electron acceptors as tetracyanoethylene (TCNE), tetracyanoquinodimethane (TCNQ) and its mono-and diannulated 1,2,5-thiadiazole derivatives ((SN2)TCNQ and (SN2)TCNQ(N2S)) (E½~ 0 -+0.2 V vs SCE in MeCN, 25,26 ), close to that of pyrazine-2,3-dicarbonitrile (Pyz(CN)2, -1.09 V vs SCE in pyridine 22 ). This indicates that the 1,2,5-thiadiazole fragment and two cyano groups induce a strong positive shift of the first reduction potential only when they are combined with the electron-deficient pyrazine ring.…”
mentioning
confidence: 64%
“…The formation of 1:1 complexes between thiadiazoles 168 and 169 with p-xylene, durene, 2,6-and 2,7-dimethylnaphthalene has been observed and their crystal structure was confirmed by X-ray analysis. 188 Treatment Recently, it was discovered that [1,2,5]thiadiazolo [3,4-c] [1,2,5]thiadiazole (21) formed charge-transfer 1:1 complex 174 with TTF in the form of air and thermally stable single crystals (Scheme 84). 42 The structure of this complex was determined by X-ray diffraction.…”
Section: Scheme 78mentioning
confidence: 99%